The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1007/s00421-017-3540-1
|View full text |Cite
|
Sign up to set email alerts
|

High-intensity aerobic interval training improves aerobic fitness and HbA1c among persons diagnosed with type 2 diabetes

Abstract: HAIT is an effective exercise strategy to improve aerobic fitness and reduce risk factors associated with T2D.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
83
0
12

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(106 citation statements)
references
References 62 publications
11
83
0
12
Order By: Relevance
“…Similarly, in the 12-week intervention studies that were similar to our study (25, 27, 57, 59, 61), no changes within the groups were reported as being statistically superior. The importance of these initial modest improvement in adiposity following a 12-week intervention must not be overlooked as a post-hoc analysis of the Look AHEAD study (64) reported that the overweight and obese T2D participants in their intensive lifestyle intervention group who lost 10% body weight in the first year of the study, had a 20% lower risk of their study's primary outcome (a composite of death from cardiovascular causes, non-fatal acute MI, non-fatal stroke or admission to hospital for angina).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Similarly, in the 12-week intervention studies that were similar to our study (25, 27, 57, 59, 61), no changes within the groups were reported as being statistically superior. The importance of these initial modest improvement in adiposity following a 12-week intervention must not be overlooked as a post-hoc analysis of the Look AHEAD study (64) reported that the overweight and obese T2D participants in their intensive lifestyle intervention group who lost 10% body weight in the first year of the study, had a 20% lower risk of their study's primary outcome (a composite of death from cardiovascular causes, non-fatal acute MI, non-fatal stroke or admission to hospital for angina).…”
Section: Discussionsupporting
confidence: 81%
“…Notwithstanding the RT component, our study was similar to prior studies comparing HIIT and MICT in people with T2D with regards to the 12-week intervention duration (25, 27, 57, 61) and the frequency of three HIIT sessions per week (25, 27, 56, 57, 61). Although the diverse application of the HIIT variables (i.e., intensity, duration and number of bouts) across all studies limit direct comparisons, our study's HIIT variables were comparable.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…(TSAI et al, 2016;HORNBUCKLE et al, 2017;STOA et al, 2017;THUM et al, 2017). Esses por sua vez, podem interferir indiretamente na qualidade de vida, disfunção sexual, distúrbios relacionados à imagem corporal e flutuações do humor (HAHN et al, 2005;JONES et al 2011;BAZARGANIPOUR et al, 2013;BENETTI-PINTO et al, 2015;DASHTI et al, 2016;SHISHEHGAR et al, 2016;PANICO et al, 2017).…”
Section: Introductionunclassified
“…Outros autores têm relatado que o treinamento intermitente promove maior adesão e é mais efetivo para a melhora da capacidade aeróbia, adaptações hemodinâmicas e redução de fatores de riscos cardiovasculares e de índices antropométricos (TSAI et al, 2016;HORNBUCKLE et al, 2017;STOA et al, 2017;THUM et al, 2017). Por outro lado, outros autores descreveram que o treinamento aeróbio contínuo foi melhor que o treinamento aeróbio intermitente quanto à melhoria da distribuição de gordura corporal e no estímulo da absorção de glicose pela insulina (KEATING et al, 2014;MOTIANI et al, 2017 …”
Section: Introductionunclassified